AJARAN RAHASIA JNÂNASIDDHANTA - Ririet Surjandari (Naditira Widya, 2009)
Jnanasiddhanta is one of the secret doctrine of Hinduism, Siva Siddhanta in particular, and it is mentioned in the Ten Chapter of Bhuwanakooea. The text stated that not until sadaka pay a large sum of learning fee to his teacher that he was taught the secret doctrine everyday; the term for the payment is gurutyaga (or guruyaga). It is suggested that this text was not written in detail and considered to be a mere teaching guidelines for the guru. This article discusses the translation and explanation of Jnanasiddhanta.